Thermal stress impaired expression of insulin-like growth factor binding proteins in pigs - BORAH, S; SOREN, S; TALUKDAR, R; KALITA, L; PAME, K; NATH, A J; BORAH, B; PATHAK, P K; BHATTACHARRYYA, B N (The Indian Journal of Animal Sciences, 2023)
This study aimed to investigate the correlation of IGFs, IGFBPs, and IGFBPRs of grower pigs with change in temperature humidity index (THI). THI was calculated to know the months of the year when pigs feel discomfort and samples of feed offered were analyzed to know the nutritional availability/deficit. The calculated average THI was above thermal comfort zone for seven months in a year. It was observed that crude protein (CP) and metabolizable energy (ME) availability to pigs were deficient. Gilts of two months age and similar body weight were randomly divided into two groups (n=6); viz. Con-fed animals (feed offered by the farmer) and For-fed animals (formulated feed supplement + Con-fed). The composition of formulated feed supplement was dried leaf of Moringa oleifera, soybean meal, rice mill waste, and mineral mixture. The plasma cortisol level increased in the experimental animals with accelerated THI as evidenced by the strong positive correlation of THI with HSP70 and HSP90. The level of leptin and ghrelin did not have significant relation with the expression level of HSPs in the present study, however, in the control animals, a low level of leptin was observed. The correlation between the growth factors and HSPs was not significant. During the season, where the THI was above the thermal comfort zone, the IGFBPR and IGFBP concentrations were non-significantly increased along with the increased THI.